Produksi Kerupuk Ubi Berbasis Kearifan Lokal: Analisis Proses, Faktor Kualitas dan Strategi Pengembangan UMKM Unggulan Desa Silungkang Duo, Kecamatan Silungkang, Kota SawahLunto - Zul Afdal; Diga Triansyah; Divya Ardita Putri; Anisa Latifah; Bimo Satria; Asep Saputra (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2026)
Cassava crackers are a traditional food product that has been passed down through generations in Silungkang Duo Village and is now recognized as one of the village's leading products. This study aims to analyze in-depth the cassava cracker production process carried out by the local community, identify factors that influence product quality, and examine the obstacles faced by micro, small, and medium enterprises (MSME) in maintaining production continuity. The approach used was descriptive qualitative with data collection techniques including in-depth interviews, participatory observation, and field documentation. The main informant was Azwir, the Head of Talang Tuluih Hamlet and a cassava cracker entrepreneur who has run the business for generations. The research findings indicate that the cassava cracker production process includes six main stages: raw material cultivation, initial processing, dough milling and fermentation, traditional molding, natural drying, and distribution and marketing. Product quality is influenced by the quality of the raw materials, fermentation duration and technique, weather conditions during drying, and workforce competency. The main obstacles that arise include dependence on weather, limited production technology, and inconsistent raw material quality. Nevertheless, cassava crackers from Silungkang Duo Village have a competitive advantage in the form of a distinctive taste and texture resulting from a traditional fermentation process. This article recommends the implementation of appropriate technology, process standardization, and expansion of marketing networks as sustainable development strategies.